Progression of two Progressive Supranuclear Palsy phenotypes with comparable initial disability. (September 2019) - Shoeibi, Ali; Litvan, Irene; Tolosa, Eduardo; Ser, Teodoro del; Lee, Euyhyun; ,
Abstract: Introduction: To avoid bias and optimize statistical power of disease-modifying therapeutic trials, it is critical to include homogeneous populations with similar rate of progression over time. Patients with Progressive Supranuclear Palsy (PSP)-Parkinsonism phenotype have overall slower disease progression than those with PSP-Richardson syndrome phenotype. However, it is unclear if the progression rate of PSP-Parkinsonism is the same when the PSP-Parkinsonism converts to PSP Richardson syndrome. We aimed to determine and compare disease progression rate of patients with the two most common PSP phenotypes: PSP-Parkinsonism and PSP Richardson syndrome, participating in the TAUROS trial. Methods: 138 patients, 56 with PSP-Parkinsonism and 82 with PSP-Richardson syndrome, with similar clinical severity at baseline, were followed up to 60 weeks. PSP-Parkinsonism allocation was based on experts' judgement and PSP-Richardson on probable NINDS-PSP criteria. Global disease progression was measured by the PSP Rating Scale as primary outcome measure and several secondary outcome measures. Results: PSP-Richardson syndrome patients had significantly faster progression based on the primary and three secondary outcome measures: the Dementia Rating Scale-2, Frontal Assessment Battery, and lexical fluency scale. Analyses including only patients with a baseline symptom duration under five years showed similar results. PSP phenotype was the strongest predictor for disease progression. Conclusion: This research showed that even when disease severity and clinical features at baseline are similar, patients with PSP- Richardson syndrome progressed significantly faster than those with PSP-Parkinsonism. Therefore, unless stratified by phenotype, future therapeutic clinical trials should not lump PSP patients with these phenotypes as a single disorder even if they have similar disease severity at screening. Highlights: Patients with PSP-Richardson progressed faster than those with PSP-Parkinsonism despite similar disease severity at baseline. PSP phenotype was the strongest predictor of disease progression. To avoid bias, future PSP trials would benefit from stratifying PSP patients with PSP-Richardson and PSP-P by phenotype.